Polymer composites with carbonaceous nanofillers : propterties and applications - Sie, Chin Tjong (Wiley-VCH, 2012)
Written by an expert in the field of nanomaterials, composites, and polymers, this book provides up-to-date information on recent advances in various aspects of polymer composites reinforced by carbonaceous nanofillers, including their fabrication and their electrical, thermal, and mechanical properties